A Novel Strategy to Enhance Mesenchymal Stem Cell Migration Capacity and Promote Tissue Repair in an Injury Specific Fashion. Issue 3 (March 2013) - Xinaris, C.; Morigi, M.; Benedetti, V.; Imberti, B.; Fabricio, A. S.; Squarcina, E.; Benigni, A.; Gagliardini, E.; Remuzzi, G.
Mesenchymal stem cells (MSCs) of bone marrow origin appear to be an attractive candidate for cell-based therapies. However, the major barrier to the effective implementation of MSC-based therapies is the lack of specific homing of exogenously infused cells and overall the inability to drive them to the diseased or damaged tissue. In order to circumvent these limitations, we developed a preconditioning strategy to optimize MSC migration efficiency and potentiate their beneficial effect at the site of injury. Initially, we screened different molecules by using an in vitro injury–migration setting, and subsequently, we evaluated the effectiveness of the different strategies in mice with acute kidney injury (AKI). Our results showed that preconditioning of MSCs with IGF-1 before infusion improved cell migration capacity and restored normal renal function after AKI. The present study demonstrates that promoting migration of MSCs could increase their therapeutic potential and indicates a new therapeutic paradigm for organ repair.